Virological and Immunological Status of the People Living with HIV/AIDS Undergoing ART Treatment in Nepal. (28th July 2016) - Ojha, Chet Raj; Shakya, Geeta; Dumre, Shyam Prakash
Abstract : Antiretroviral therapy (ART) has increased the life span of the people living with HIV (PLHIV), but their virological and immunological outcomes are not well documented in Nepal. The study was conducted at a tertiary care center including 826 HIV-1 seropositive individuals undergoing ART for at least six months. Plasma viral load (HIV-1 RNA) was detected by Real Time PCR and CD4 + T-lymphocyte (CD4 + ) counts were estimated by flow cytometry. The mean CD4 + count of patients was 501 (95% CI = 325–579) cells/cumm, but about 35% of patients had CD4 + T cell counts below 350 cells/cumm. With increasing age, average CD4 + count was found to be decreasing (p = 0.005 ). Of the total cases, 82 (9.92%) were found to have virological failure (viral load: >1000 copies/ml). Tenofovir/Lamivudine/Efavirenz (TDF/3TC/EFV), the frequently used ART regimen in Nepal, showed virological failure in 11.34% and immunological failure in 37.17% of patients. Virological failure rate was higher among children < 15 years (14.5%) (p = 0.03 ); however, no association was observed between ART outcomes and gender or route of transmission. The study suggests there are still some chances of virological and immunological failures despite the success of highly active ART (HAART).